2013
DOI: 10.1037/a0030746
|View full text |Cite
|
Sign up to set email alerts
|

Investment and intellect: A review and meta-analysis.

Abstract: Cognitive or intellectual investment theories propose that the development of intelligence is partially influenced by personality traits, in particular by so-called investment traits that determine when, where, and how people invest their time and effort in their intellect. This investment, in turn, is thought to contribute to individual differences in cognitive growth and the accumulation of knowledge across the life span. We reviewed the psychological literature and identified 34 trait constructs and corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
271
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(318 citation statements)
references
References 206 publications
(232 reference statements)
27
271
1
2
Order By: Relevance
“…We were able to replicate the typically found positive linear associations between emotional stability and openness and cognitive skills and the negative association between conscientiousness and cognitive skills (Ackerman and Heggestad 1997;DeYoung 2011;Chamorro-Premuzic and Furnham 2005;Von Stumm and Ackerman 2013). Results of the quadratic analyses demonstrated that the results for emotional stability and openness were primarily triggered by comparatively low performance in the competency measures of persons who were low on emotional stability or openness, respectively.…”
Section: Discussionsupporting
confidence: 57%
“…We were able to replicate the typically found positive linear associations between emotional stability and openness and cognitive skills and the negative association between conscientiousness and cognitive skills (Ackerman and Heggestad 1997;DeYoung 2011;Chamorro-Premuzic and Furnham 2005;Von Stumm and Ackerman 2013). Results of the quadratic analyses demonstrated that the results for emotional stability and openness were primarily triggered by comparatively low performance in the competency measures of persons who were low on emotional stability or openness, respectively.…”
Section: Discussionsupporting
confidence: 57%
“…This suggests that imagination and aesthetic sensitivity could be more related to engaging in regular reading habits that in turn could develop language skills, whereas order and discipline could be more important for the persistence and repeated practice necessary for developing the complex acquaintance underlying math knowledge. These findings suggest the intriguing hypothesis that C and O have unique moderation effects in the process of investment of potential abilities into learning activities that turn potential into crystalized knowledge (Von Stumm & Ackerman, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…One focused on artistic qualities and fantasy, and the other focused on innovativeness and intellectual curiosity. The finding that openness comprises at least two distinct lower order trait dispositions has been described in literature (see Von Stumm & Ackerman, 2013). We included the subscale focusing on innovativeness and intellectual curiosity, since we deemed this construct more relevant for the professional context.…”
Section: Ability Motivation and Intellectual Curiosity Variablesmentioning
confidence: 99%